IMPLEMENTATION OF CHANGE MANAGEMENT POLICY TO DEVELOP VILLAGE-OWNED BUSINESS ENTITIES - Dwiningwarni, Sayekti Suindyah; Andari, Syamsiyah Yuli Dwi; Sujani, Sujani; Shodiq, Ja'far; Chamariyah, Chamariyah; Dwi P, Juniyanti (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
This research aims to identify internal and external factors in implementing BUMDes change management policies; to identify the changes that have occurred in BUMDes by using the theory of Lewin's Three-Step Model and Kotter's 8 Step Change Model; formulate a policy strategy for the development of BUMDes. The research method used is mixed. The data used are qualitative data from in-depth interviews and secondary data in one district in East Java province. Data analysis used sequential exploratory. The results of the study explain that the management changes that occur in the developing phase to the managing are first, for all BUMDes to immediately reorganize BUMDes managers by Regional Regulation Number 6 of 2021; second, the management changes that occur from the managing phase to the transformation are the need for a BUMDes consultant or assistant as a change agent to help develop BUMDes from different sides; third, the results of the SWOT analysis show that there are three main strategies needed to establish BUMDes, namely the business unit development strategy, facilities strategy and service strategy. This research concludes that implementing change management policies is essential to developing BUMDes.JEL: M210, H100, L100.